Effects of curcumin on ion channels and transporters - Zhang, Xuemei; Chen, Qijing; Wang, Yunman; Peng, Wen; Cai, Hui (Frontiers in Physiology, 2014)
Curcumin [1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione], a polyphenolic compound isolated from the rhizomes of Curcuma longa (turmeric), has been shown to exhibit a wide range of pharmacological activities including anti-inflammatory, anti-cancer, anti-oxidant, anti-atherosclerotic, anti-microbial and wound healing effects. These activities of curcumin are based on its complex molecular structure and chemical features, as well as its ability to interact with multiple signaling molecules. The ability of curcumin to regulate ion channels and transporters was recognized a decade ago. The cystic fibrosis transmembrane conductance regulator (CFTR) is a well-studied ion channel target of curcumin. During the process of studying its anti-cancer properties, curcumin was found to inhibit ATP-binding cassette (ABC) family members including ABCA1, ABCB1, ABCC1 and ABCG2. Recent studies have revealed that many channels and transporters are modulated by curcumin, such as voltage-gated potassium (Kv) channels, high-voltage-gated Ca2+ channels (HVGCC), volume-regulated anion channel (VRAC), Ca2+ release-activated Ca2+ channel (CRAC), aquaporin-4 (AQP-4), glucose transporters, etc. In this review, we aim to provide an overview of the interactions of curcumin with different types of ion channels and transporters and to help better understand and integrate the underlying molecular mechanisms of the multiple pharmacological activities of curcumin.